Standups - Griffiths, Dawn; Griffiths, David, 1969- (O'Reilly Media, 2018)
"In an Agile project, planning is a continuous process. From start to finish, the team continually makes small adjustments to what they do with the help of 'standups': short planning sessions held at the start of every day. This clip is originally from The Agile Sketchpad video course."--Resource description page